Complex motivated behaviors for natural rewards following a binge-like regimen of morphine administration: mixed phenotypes of anhedonia and craving after short-term withdrawal - Bai, Yunjing; Li, Yingying; Lv, Yaodi; Liu, Zhengkui; Zheng, Xigeng (Frontiers in Behavioral Neuroscience, 2014)
The anhedonia-like behaviors following about 1-week withdrawal from morphine were examined in the present study. Male rats were pretreated with either a binge-like morphine paradigm or daily saline injection for 5 days. Three types of natural reward were used, food reward (2.5, 4, 15, 30, 40, and 60% sucrose solutions), social reward (male rat) and sexual reward (estrous female rat). For each type of natural stimulus, consummatory behavior and motivational behaviors under varied testing conditions were investigated. The results showed that the morphine-treated rats significantly reduced their consumption of 2.5% sucrose solution during the 1-h consumption testing and their operant responding for 15, 30, and 40% sucrose solutions under a fixed ratio 1 (FR1) schedule. However, performance under a progressive ratio (PR) schedule increased in morphine-treated rats reinforced with 60% sucrose solution, but not in those reinforced with sucrose concentrations lower than 60%. Pretreatment with morphine significantly decreased the male rats' ejaculation frequency (EF) during the 1-h copulation testing, and impaired the maintenance of appetitive motivations to sexual and social stimuli under a free-approach condition. Moreover, the morphine-treated rats demonstrated a diminished motivation to approach social stimulus in the effort-based appetitive behavior test but showed a remarkable increase in motivation to approach sexual stimulus in the risky appetitive behavior test. These results demonstrated some complex motivated behaviors following about 1 week of morphine withdrawal: (1) The anhedonia-like behavior was consistently found in animals withdrawn from morphine. However, for a given reward, there was often a dissociation of the consummatory behaviors from the motivational behaviors, and whether the consummatory or the motivational anhedonia-like behaviors could be discovered heavily depended on the type and magnitude of the reward and the type of testing task; (2) These anhedonia-like behaviors coexisted with a craving for the high-incentive reward which was evidenced by the increased PR performance for the 60% sucrose solution and the heightened risky appetitive behavior for the sexual stimulus. The craving for the high-incentive reward alongside with the impaired inhibitory control in drug-withdrawn subjects might form one of psychological mechanisms underlying drug relapse after withdrawal.